Further Developments in Dynamic Modelling of CO2 Capture from Flue Gas. Issue 1 (2015) - Dickinson, Jillian; Puxty, Graeme; Percy, Andrew; Vincent Verheyen, T.
Abstract: Mathematical modelling of CO2 capture from industrial flue gas by absorption into amine solutions such as monoethanolamine (MEA) has been undertaken for decades and steady state, rate-based and dynamic models have been constructed to predict the changes in the process. Recently, dynamic models have been used to predict the effect that physical operational changes have on the absorption process. As more is learnt about the chemistry of MEA and CO2 it becomes evident that the absorption system is losing available MEA, by degradation and by vaporization into the gaseous phase. This paper describes a dynamic model of the absorber column that can be used to predict the reduction of available MEA, the loss of MEA to the atmosphere, and the build-up of heat stable salts. The proposed mathematical model consists of a system of partial differential equations to represent the change of each component with height of the column and with time. It has been validated with data from a pilot capture plant located at the brown coal fired Loy Yang power station in Australia.